فاعلية إستراتيجية فكر ، زاوج ، شارك في تدريس وحدة من مقرر الرياضيات على التحصيل الدراسي و التفكير الرياضي لدى طلاب الصف السادس الابتدائي في مدينة جدة - المالكي، عبدالملك بن مسفر بن حسن (جامعة الأزهر - كلية التربية, 2012)
هدفت هذه الدراسة إلى معرفة فاعلية إستراتيجية(فكر – زاوج – شارك) في تدريس وحدة من مقرر الرياضيات على التحصيل الدراسي والتفكير الرياضي لدى طلاب الصف السادس الإبتدائي في مدينة جدة، وتحقيقا لهذا الهدف تم إستخدام المنهج التجريبي، طبقت الدراسة على عينة من طلاب الصف السادس بمدرسة الأمير متعب بمدينة جدة بلغ عددهم(56) طالبا، تم تقسيمهم إلى مجموعتين:مجموعة تجريبية بلغ عددهم(28) طالبا، ومجموعة تجريبية بلغ عددهم(28) طالبا، وقد تم قياس أداء طلاب المجموعتين:الضابطة والتجريبية قبليا وبعديا بواسطة إختباري التحصيل والتفكير الرياضي، تم إستخدام إختبار"ت" لإختبار فروض الدراسة، وقد توصلت الدراسة إلى النتائج التالية: \\\\ 1-\\\\\\\ توجد فروق ذات دلالة إحصائية عند مستوى0.05بين متوسطي درجات تلاميذ المجموعتين:التجريبية والضابطة في الإختبار التحصيلي البعدي لصالح المجموعة التجريبية. \\\\ 2-\\\\\\\ توجد فروق ذات دلالة إحصائية عند مستوى0.05بين متوسطي درجات تلاميذ المجموعتين:التجريبية والضابطة في إختبار التفكير الإستقرائي البعدي لصالح المجموعة التجريبية. \\\\ 3-\\\\\\\ توجد فروق ذات دلالة إحصائية عند مستوى0.05بين متوسطي درجات تلاميذ المجموعتين:التجريبية والضابطة في إختبار التفكير الإستنتاجي البعدي لصالح المجموعة التجريبية. \\\\ 4-\\\\\\\ توجد فروق ذات دلالة إحصائية عند مستوى0.05بين متوسطي درجات تلاميذ المجموعتين:التجريبية والضابطة في إختبار التعميم البعدي لصالح المجموعة التجريبية. \\\\ 5-\\\\\\\ توجد فروق ذات دلالة إحصائية عند مستوى0.05بين متوسطي درجات تلاميذ المجموعتين:التجريبية والضابطة في إختبار التعبير بالرموز البعدي لصالح المجموعة التجريبية. \\\\ 6-\\\\\\\ توجد فروق ذات دلالة إحصائية عند مستوى0.05بين متوسطي درجات تلاميذ المجموعتين:التجريبية والضابطة في إختبار المنطق الرياضي البعدي لصالح المجموعة التجريبية. \\\\ وفي ضوء نتائج الدراسة تم تقديم عدد من التوصيات من أهمها: \\\\ 1-\\\\\\\ ضرورة إعادة النظر في مقررات مادة الرياضيات في المرحلة الإبتدائية بحيث تركز على تنمية التفكير بجميع أنواعه، وخاصة التفكير الرياضي والبعد عن التركيز على الحفظ والإستظهار للمعلومات والمعارف الرياضية. \\\\ 2-\\\\\\\ ضرورة إعادة صياغة مقررات الرياضيات في المرحلة الإبتدائية بما يتناسب وخصائص طلاب المرحلة، والتركيز على دور الطالب وفاعليته في إكتساب المعرفة والمهارات الرياضية المختلفة بحيث يصبح دور المعلم التوجيه والمتابعة. \\\\ 3-\\\\\\\ أهمية تدريب معلمي الرياضيات في المرحلة الإبتدائية على إستخدام إستراتيجيات التدريس الحديثة ومنها التعلم النشط وإستراتيجياته المختلفة ومنها إستراتيجية(فكر – زاوج – شارك). Study Title: The activity of (Think-orchestrate-participate) strategy in teaching Mathematics and its influence on understanding and mathematical thinking for 6th grade students in Jeddah.This study aims at realizing the activity of (Think-orchestrate-participate) strategy in teaching Mathematics and its influence on understanding and mathematical thinking for 6th grade students in Jeddah. To achieve this I have used trial way that I have applied on 56 students in Prince Meteeb School in Jeddah. Students were divided into 2 groups each one consists of 28 students measuring the performance of two students before and after the trial by gaining and Mathematical exam. The exam used was "C" and the results are: \\\\ 1-\\\\\\\ There were statistically significant differences at the 0.05 level between the average grades of the two groups: experimental and control groups in the post achievement test for the experimental group. \\\\ 2-\\\\\\\ There\\\\\\\ were\\\\\\\ statistically .significant differences at the 0.05 level between the average grades of the two groups: experimental and control groups in dimensional inducting thinking test for the experimental. \\\\ 3-\\\\\\\ There\\\\\\\ were statistically significant differences at the 0.05 level between the average grades of the two groups: experimental and control groups in the post test circular for the experimental. \\\\ 4-\\\\\\\ There were statistically significant differences at the 0.05 level between\\\\\\\ the\\\\\\\ average\\\\\\\ grades\\\\\\\ of\\\\\\\ the\\\\\\\ two groups: experimental and control groups in dimensional deductive thinking test circular for the experimental. \\\\ 5-\\\\\\\ There were statistically significant differences at the 0.05 level between\\\\\\\ the average\\\\\\\ grades\\\\\\\ of\\\\\\\ the\\\\\\\ two groups: experimental and control groups in dimensional generalizations test circular for the experimental. \\\\ 6-\\\\\\\ There\\\\\\\ were statistically significant differences at the 0.05 level between\\\\\\\ the average grades of the two groups: experimental and control groups in symbolic expression test circular for the experimental. \\\\ 7-\\\\\\\ There\\\\\\\ were statistically significant differences at the 0.05 level between\\\\\\\ the\\\\\\\ average\\\\\\\ grades\\\\\\\ of\\\\\\\ the\\\\\\\ two groups: experimental and control groups in dimensional Mathematical logic test circular for the experimental. \\\\ Hence ‘some recommendations were presented: \\\\ 1- Need to reconsider the decisions of mathematics in primary school in order to focus on the development of thinking of all kinds ‘especially mathematical thinking and away from a focus on conservation and memorization of sports information and knowledge. \\\\ 2-The bad need to reformulate the math textbooks at the primary level ‘commensurate with the characteristics of students ‘and a focus on the role and effectiveness of the student in the acquisition of knowledge and skills of various sports so that the role of the teacher is guidance and follow- up. \\\\ 3- The importance of training teachers of mathematics in primary school on the use of modern teaching strategies and active learning and various strategies ‘including the strategy (Think - Orchestrate - Participate).
Keywords: طلاب المدارس الابتدائية -- العملية التعليمية -- طرق التدريس -- تدريس الرياضيات -- التحصيل الدراسي -- معلمو الرياضيات -- جدة -- السعودية -- سلوك الطلاب